Global Contestations of Gender Rights - Scheele, Alexandra; Roth, Julia; Winkel, Heidemarie (Kultur und soziale Praxis, 2022)
Across the globe, a growing number of social movements, such as demonstrations in support of equal civil status or reproductive freedom and against sexualized violence, show that women's and gender rights are highly contested. Against the backdrop of a long history of unequal rights implementation, the contributors to this volume deal with the questions of why and in which ways gender equality has become contested in various political contexts. Local case studies examine the relevant structural, institutional, and socio-cultural causes of the global challenges to equality. This book follows an interdisciplinary approach and unites scholars from law, linguistics, cultural studies, history, social sciences, and gender studies in diverse contexts.